مدى إمكانية استخدام تكنولوجيا مؤتمرات الفيديو في الإشراف التربوي من وجهة نظر المشرفين في سلطنة عمان - ندابي، محمد حمد (Kulliyah of Education, International Islamic University Malaysia, 2021)
This study aims to identify the views of educational supervisors on the extent to which video conference technology can be used in educational supervision processes, knowledge of this concept, its importance, the obstacles facing this application and the proposed solutions from the viewpoint of the educational supervisors at the Ministry of Education in the Sultanate of Oman, to expand their knowledge about the use of video conferencing technology. As a modern supervisory model, its importance in educational supervision, its applications in supervision processes and the obstacles facing this use and the proposed solutions. And the identification of statistically significant differences in the degree of possibility of using videoconferencing due to different variables (educational governorate, academic qualification, specialization, job title, years of experience, number of courses in dealing with a computer / the Internet). To achieve the study objectives, the researcher adopts the descriptive approach. Analytical, using the questionnaire as a tool to collect data as a tool for studying it after making sure of its validity and consistency. It was applied to an intended sample of (322) supervisors, and the researcher used the interview with (8) of the general supervisors, (12) of the first supervisors and (15) from the educational supervisors, to learn about the suggested ways to face these obstacles. The study concluded with a set of study results, the most important of which are: The concept of supervision using videoconferencing technology is clear to educational supervisors largely, the views of the educational supervisors were broadly agreed on the importance of using video conferencing technology in educational supervision processes, from the educational supervisors' point of view, the degree of possibility of using video conference technology in educational supervision came to a large extent, and the most significant material obstacles that prevent supervisors from using video conferencing technology in educational supervision are weak communication networks and the Internet and poor infrastructure for the application of this technology, while the human challenges lie in the lack of adequate training to use this technology.